Single mother role in the family - Iin Tata Maranatha br Hutasoit; Karina Meriem Beru Brahmana (Indonesian Institute for Counseling, Education and Theraphy, 2021)
A single mother family is a family in which there is only one parent, the mother, who cares for her children without the help of her husband since they have separated. This separation might be the result of death or divorce. This makes the life of a single mother more challenging, resulting in life difficulties.The goal of the literature study is to examine the living situations of single mother families in which the mother is the sole provider. Methods:A literature review is conducted on the basis of data collected from many papers and journals.Articles were gathered using the search engine Google Scholar.The requirements for articles are those published between 2015 and 2020.According to the report, the living conditions of single mothers are harsh; they face pressure and demands that make it impossible for them to fulfill their responsibilities. In light of the fact that single mothers have a more difficult existence than those with intact families, it is expected that they are more capable of overcoming obstacles and maintaining family life.